Examples

Example 1
Important

Example 2 Important

Example 3 Important

Example 4

Example 5

Example 6 Important

Example 7

Example 8 Important

Example 9

Example 10

Example 11 (i) Important

Example 11 (ii) Important

Example 12 Important

Example 13

Example 14 Important

Example 15

Example 16 Important

Example 17

Example 18 Important

Example 19

Example 20

Example 21 Important

Example 22

Example 23 Important

Example 24

Example 25 Important

Example 26

Example 27 Important

Example 28 Important You are here

Example 29 Important

Example 30 Important

Example 26 (Supplementary NCERT) Deleted for CBSE Board 2022 Exams

Example 27 (Supplementary NCERT) Deleted for CBSE Board 2022 Exams

Example 28 (Supplementary NCERT) Important Deleted for CBSE Board 2022 Exams

Example 29 (Supplementary NCERT) Important Deleted for CBSE Board 2022 Exams

Example 30 (Supplementary NCERT) Important Deleted for CBSE Board 2022 Exams

Example 31 (Supplementary NCERT) Important Deleted for CBSE Board 2022 Exams

Last updated at May 6, 2021 by Teachoo

Example 28 Let π β, π β and π β be three vectors such that |π β|= 3, |π β|= 4, |π β|= 5 and each one of them being perpendicular to the sum of the other two, find |π β" + " π β" + " π β |.Given, |π β| = 3 , |π β| = 4 , |π β|= 5 Also, Each one of them being perpendicular to the sum of the other two π β is perpendicular to π β + π β π β. (π β + π β) = 0 π β. π β + π β. π β = 0 π β is perpendicular to π β + π β π β. (π β + π β) = 0 π β. π β + π β. π β = 0 π β is perpendicular to π β + π β π β. (π β + π β) = 0 π β. π β + π β. π β = 0 Now, |π β+π β+π β |2 = (π β + π β + π β) . (π β + π β + π β) = π β. π β + π β . π β + π β . π β + π β . π β + π β . π β + π β . π β + π β . π β + π β . π β + π β . π β = π β. π β + (π β . π β + π β . π β) + π β . π β + (π β . π β + π β . π β) + π β . π β + (π β . π β + π β . π β = π β. π β + (0) + π β . π β + (0) + π β . π β + (0) = π β. π β + π β. π β + π β. π β = "|" π β"|"2 + "|" π β"|"2 + "|" π β"|"2 = 32 + 42 + 52 = 9 + 16 + 25 = 50 So, |π β+π β+π β |2 = 50 Taking square root both sides, "|" π β "+ " π β" + " π β"|" = β50 "|" π β "+ " π β "+ " π β"|" = β25 Γ β2 "|" π β "+ " π β "+ " π β"|" = πβπ = π β. π β + (0) + π β . π β + (0) + π β . π β + (0) = π β. π β + π β. π β + π β. π β = "|" π β"|"2 + "|" π β"|"2 + "|" π β"|"2 = 32 + 42 + 52 = 9 + 16 + 25 = 50 So, |π β+π β+π β |2 = 50 Taking square root both sides, "|" π β "+ " π β" + " π β"|" = β50 "|" π β "+ " π β "+ " π β"|" = β25 Γ β2 "|" π β "+ " π β "+ " π β"|" = πβπ